Synthesis and Antioxidant Activity of Some 3-Aroyl Chromanone and Flavanones - Wankhade, B.B.; Saoji, V.N.; Chaple, D.R.; Bharambe, C.M. (Asian Journal of Chemistry, 2010)
Flavanones and chromanones are known to be biologically important compounds. In the present work two 3-aroyl flavanones and one 3-aroyl chromanone were prepared from phenol and p-cresol as starting material. The compounds were characterized on the basis of elemental and spectral analysis and were screened for their antioxidant activity by DPPH method. The compounds exhibit antioxidant activity in the range of 8-11 mg mL-1 concentration. The activity was corelated with the structure. It is observed that the antioxidant activity increases with substitution of -OCH3 and furyl groups.